2021
DOI: 10.3389/fneur.2021.679881
|View full text |Cite
|
Sign up to set email alerts
|

MRI Prognostic Factors in Multiple Sclerosis, Neuromyelitis Optica Spectrum Disorder, and Myelin Oligodendrocyte Antibody Disease

Abstract: Several MRI measures have been developed in the last couple of decades, providing a number of imaging biomarkers that can capture the complexity of the pathological processes occurring in multiple sclerosis (MS) brains. Such measures have provided more specific information on the heterogeneous pathologic substrate of MS-related tissue damage, being able to detect, and quantify the evolution of structural changes both within and outside focal lesions. In clinical practise, MRI is increasingly used in the MS fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 137 publications
0
10
0
Order By: Relevance
“…In ADEM, MRI lesions completely or partially resolve for up to 90% of patients 51 . A 2021 article nicely summarized the currently known factors on imaging for MS, NMO, and MOG-associated disease, 52 as shown in figure 11-6 . Asymptomatic lesions are seen in MS, whereas in NMOSD, this only rarely occurs 53 …”
Section: Role Of Mri In Prognosis Treatment and Outcomementioning
confidence: 99%
“…In ADEM, MRI lesions completely or partially resolve for up to 90% of patients 51 . A 2021 article nicely summarized the currently known factors on imaging for MS, NMO, and MOG-associated disease, 52 as shown in figure 11-6 . Asymptomatic lesions are seen in MS, whereas in NMOSD, this only rarely occurs 53 …”
Section: Role Of Mri In Prognosis Treatment and Outcomementioning
confidence: 99%
“…The delayed diagnosis and treatment might be the critical factors. Previous studies found that tetraparesis and long spinal cord lesions were associated with long-term disability ( 12 , 13 ). Since our case presented with these poor prognostic factors, follow-up is required to define the long-term prognosis.…”
Section: Discussionmentioning
confidence: 95%
“…The frequency-domain 31 P spectra were analyzed by lineshape fitting (Figure S2, Supporting Information) using an in-house program written in MATLAB (MathWorks, Natick, MA, USA). Typically all 31 P peaks were fitted using a single-Gaussian lineshape model with inclusion of prior knowledge of metabolite chemical shifts and resonance patterns as soft constraints when approperiate 17,[43][44][45] Lineshape deconvolution was performed for P i and β-ATP signals with asymmetric appearance or line splitting, using two separate Gaussian components with different chemical shifts. The average chemical shift of such signal was determined by the population-weighted chemical shift δ = c 1 δ 1 + c 2 δ 2 , where c 1 and c 2 are the relative populations of the two components (c 1 + c 2 = 1).…”
Section: Discussionmentioning
confidence: 99%
“…This study is carried out on a cohort of pediatric patients with myelin oligodendrocyte glycoprotein antibody‐associated disorders (MOGADs)—an idiopathic, inflammatory, demyelinating condition of the central nervous system (CNS), with high prevalence in young adults and heterogeneity in individual symptoms, radiological manifestations and clinical course 40–42 . MOGAD lesions are often non‐specific on conventional MRI; the diagnosis at the initial presentation requires an accurate serum antibody test 42,43 . Currently, there is still a lack of understanding of the molecular, biochemical, and cellular mechanisms that cause specific lesions to form, though several energy abnormalities are considered to be present at the sites of demyelination 44–46 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation